2014
DOI: 10.2174/1570159x11666131120223201
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Eased Cognitive Impairment Induced by Chronic L-methionine Administration: Potential Role of Oxidative Stress

Abstract: Chronic administration of L-methionine leads to memory impairment, which is attributed to increase in the level of oxidative stress in the brain. On the other hand, metformin is a commonly used antidiabetic drug with strong antioxidant properties. In the current study, we tested if chronic metformin administration prevents memory impairment induced by administration of L-methionine. In addition, a number of molecules related to the action of metformin on cognitive functions were examined. Both metformin and L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 41 publications
0
24
0
5
Order By: Relevance
“…But research of its role in cognitive function has produced controversial findings. Some studies have reported beneficial effects of metformin on memory function in mice (41)(42)(43)(44). Other studies, however, point to its role in the increased risk for AD and potential adverse effects on the cognitive performance of diabetic patients, in which scenario metformin is a routine prescription (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…But research of its role in cognitive function has produced controversial findings. Some studies have reported beneficial effects of metformin on memory function in mice (41)(42)(43)(44). Other studies, however, point to its role in the increased risk for AD and potential adverse effects on the cognitive performance of diabetic patients, in which scenario metformin is a routine prescription (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…GSH levels in brain and spinal cord did not differ compared to control. This attenuation proves the antioxidant property of MET [Pintana et al, ; Alzoubi et al, ]. MET activates AMPK, which has a crucial role in stabilizing mitochondrial membrane potential, decreasing endoplasmic reticulum stress along with ROS production consequently avoiding the oxidative damage [Barreto‐Torres et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin had no effect on spatial learning. Other studies have shown improved cognitive performance with metformin using similar testing paradigms [18, 49, 50]. Interestingly, a sub group analysis of participants from the Primary Research in Memory Clinics study showed that among patients with diabetes, worse cognitive performance was associated with metformin use [51].…”
Section: Discussionmentioning
confidence: 99%